Аналіз моделей для оцінювання впливу поверхневого ефекту на величину активного опору суцільних та багатопроволочних жил силових кабелів - Костюков, Іван Олександрович; Гонтар, Юлія Григорівна (Національний технічний університет "Харківський політехнічний інститут", 2020)
У статті проведено аналіз деяких розрахункових співвідношень, що використовуються для визначення впливу поверхневого ефекту на величину активного опору суцільних і багатопроволочних жил силових кабелів. Показано, що застосування розглянутих розрахункових співвідношень призводить до висновку, згідно з яким ускладнення конструкції жили силового кабелю за рахунок її виготовлення з скручених між собою дротів зменшує вплив поверхневого ефекту на опір жили в порівнянні з суцільною жилою аналогічного номінального перерізу.

The article analyzes some relations that are used in order to determine the influence of skin effect on the value of the active resistance of solid and stranded conductors of power cables. It is shown that the applying of the considered relations leads to the conclusion that the complication of the structure of the core of the power cable due to its manufacture from twisted together wires leads to the decreasing of the influence of skin effect on the resistance of power cable core in comparison with a solid core of a similar nominal cross-section. It was shown that this reduction takes place due to the calculation of the electrical resistance of power cable core based on the relation which is based on the applying of the nominal cross-section of the power cable core. In the range of core cable cross-section values from 240 mm2 to 500 mm2, despite some increase in core resistance, the influence of skin effect is not significant enough to transfer the value of the complex resistance to the region almost independent of the generalized parameter x phase angle. In the same range of values of the cross sections of the core such a transition of its complex resistance in the region of almost constant value of the phase angle can be achieved by increasing the frequency of current flowing through the core, however, this transition occurs in the frequency range much higher than the value of the industrial frequency.
An analysis of models for the estimation of the impact of skin effect on the value of active resistance of solid and multi-conductor cores of power cables
Keywords: внутрішня індуктивність; комплексний опір; internal inductance; impedance